2008
DOI: 10.1186/1749-799x-3-51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined treatment with alendronate and calcitriol on femoral neck strength in osteopenic rats

Abstract: BackgroundHip fracture is associated with pronounced morbidity and excess mortality in elderly women with postmenopausal osteoporosis. Many drugs have been developed to treat osteoporosis and to reduce the risk of osteoporotic fractures. We investigated the effects of combined alendronate and vitamin D3 treatment on bone mass and fracture load at the femoral neck in ovariectomized (OVX) rats, and evaluated the relationship between bone mass parameters and femoral neck strength.MethodsThirty 12-week-old female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…They demonstrated bone loss of about 13.8% in the distal femur and 12.1% in the proximal tibia of ovariectomized rats compared to control ones. In addition, one recent study showed a 9.5% decrease of BMD in rats after receiving ovariectomy 32 weeks later compared to rats in control group [19]. Our results of decreased BMD in ovariectomized rats were consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…They demonstrated bone loss of about 13.8% in the distal femur and 12.1% in the proximal tibia of ovariectomized rats compared to control ones. In addition, one recent study showed a 9.5% decrease of BMD in rats after receiving ovariectomy 32 weeks later compared to rats in control group [19]. Our results of decreased BMD in ovariectomized rats were consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…The adequacy of anaesthesia was monitored by the lack of the pedal withdrawal reflex, slow constant breathing, and no response to surgical manipulation. The osmotic mini-pump was changed every 4 weeks for 12 weeks, and the dose of alendronate (0.1 mg/kg/day) was chosen according to the results of previous studies [18,19].…”
Section: Animals and Reagentsmentioning
confidence: 99%
“…4g–i). At 12 weeks post-OVX, Nakamura et al [28] reported a significantly lower maximal fracture load (−29.3%), relative to the sham-control group, which was likely related to a decrease in cortical width that is typically statistically significant by approximately 90 days post-OVX [12]. …”
Section: Discussionmentioning
confidence: 99%